ECTHR_COMMITTEE 34649/19 vom 6. Juli 2023 , AFFAIRE NIKAS c. GRÈCE - Ecthr Committee (2023)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure administrative;Article 6-1 - Délai raisonnable); Violation: 6;6-1